Augmented Renal Clearance: What Have We Known and What Will We Do? - Yifan Luo; Yifan Luo; Yidan Wang; Yidan Wang; Yue Ma; Yue Ma; Puxiu Wang; Puxiu Wang; Jian Zhong; Yang Chu; Yang Chu (Frontiers Media S.A., 2021)
Augmented renal clearance (ARC) is a phenomenon of increased renal function in patients with risk factors. Sub-therapeutic drug concentrations and antibacterial exposure in ARC patients are the main reasons for clinical treatment failure. Decades of increased research have focused on these phenomena, but there are still some existing disputes and unresolved issues. This article reviews information on some important aspects of what we have known and provides suggestion on what we will do regarding ARC. In this article, we review the current research progress and its limitations, including clinical identification, special patients, risk factors, metabolism, animal models and clinical treatments, and provide some promising directions for further research in this area.